Multiple fourth molars: surgical treatment in young patient - Franciele Elias Delgado; Alan Diego Mtanyous Youssef; Tiago Jonasson; Alex Landucci; Lucienne Miranda Ulbrich; Melissa Rodrigues de Araujo (Revista Sul-Brasileira de Odontologia, 2015)
The abnormal development of one or more teeth exceeding the number considered normal is defined as hyperdontia, or supernumerary teeth. Supernumerary teeth are usually diagnosed by routine radiographs, because in most cases they are asymptomatic and do not erupt. The prevalence of supernumerary teeth is low, ranging between 0.1 and 3.8%. Objective: To report a case of multiple non-erupted fourth molars. Case report: Patient M.N.S, 16 years old, female, leucoderma, in good health status attended the dental clinic referred by the orthodontist. On panoramic radiography, the germs of the teeth #18, #28, #38 and #48 were detected and retained. Also, the presence of three forth molars distally to the teeth #18, #28 and #38 were observed. The surgical removal of all third and fourth molars was performed under local anesthesia, in two steps: left and right sides. The patient has been followed for 1 year. Fourth molar prevalence is higher in males (2:1), differing from the patient of this case report. A few cases of multiple supernumerary teeth in non-syndromic patients are reported in the literature. Conclusion: Both early diagnosis and treatment are important to prevent crowding, failure of eruption, displacement of teeth, impairment of orthodontic treatment, gingivitis, and formation of abscess, cysts, and odontogenic tumors.